Take Her, She's Yours - Jagoe, Eva-Lynn (punctum books, 2020)
We say, you belong to me, or I belong to you. But is it possible to be possessed by others? And can we ever possess ourselves? In this raw and intimate account, Eva-Lynn Jagoe merges memoir with critical theory as she recounts the unraveling of everything she thought she knew about selfhood, relationships, and desire. Through the story of an upbringing in a patriarchal Spanish and American household, a dissociative and painful relationship towards men and power, and a chaotic marriage and divorce, she interrogates the destructive fantasy of possessive individualism that permeates our psyches and our cultural expectations. Woven through this narrative is an account of the unique relationship that Jagoe has with her psychoanalyst, in which she works through her tendency to give herself away to others, and learns to navigate the many contradictory selves that we all hold within us. This journey leads her to an enriched understanding of self-possession. Jagoe's account of an examined life is inseparable from her commitment to the psychoanalytic, feminist, and queer theories that sustain and nourish her in her search for an expanded definition of self.Jagoe's unique blend of musings and reflections on literature, fairy tale, and culture; her willingness to delve into abjection and contradictory desires; and her honest portrayal of the realities of psychoanalysis allow for a timely exploration of gender, sex, and power. Take Her, She's Yours belongs in the company of Eve Kosofsky Sedgwick's A Dialogue on Love and the memoirs of Maggie Nelson, Rachel Cusk, and Lidia Yuknavitch. It engrossingly conveys the lived urgency of critical thinking and the pleasures and perils of embodied selfhood. Take Her, She's Yours is a story about loss and letting go, but also about the intimacy that emerges through an expanded definition of selfhood.